The Cerebrovascular Disease and Nutritional State. - Leticia del Rosario Cruz; Mildred Díaz Masip; Manuel Guzmán Noa; José Miguel Rodríguez Perón; Fidel Pérez Pérez; Mayelin Blanco Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: It is recognized the importance of malnutrition as a cause of morbidity and mortality in medical and surgical affections. The nutritional assessment of the patient should be based on a correct evaluation of different aspects. Objective: To assess the nutritional state of patients affected by cerebrovascular diseases in its ischemic form and the incidence of complications and deaths. Methods: A randomized simple and open clinical trial which is also prospective and longitudinal, not controlled by placebos that included 80 patients with a tomographed-clinical diagnosis of cerebral infarction admitted at the Higher Institute of Military Medicine during 2005. Clinical and dietary record, weight, size, daily assessments of the immunological performance by means of peripheral count of lymphocytes were analyzed. Results: Out of the total, 90 per cent of the patients had a weight loss lesser than 10 % of the ideal weight and, the 10% made evident a discrete increasing of weight. Patients with complications presented higher per cent of loss of weight and higher figures of urinary nitrogen. The higher per cent of loss of weight and the lowest lymphocytes count were found in patients with septic complications. An abbaissement in adequate nutritional parameters was found in deceased patients. Significant differences in the report of the initial malnourished patient's complication existed. Conclusions: It was evident the relationship between the evolution of the cerebrovascular disease and the nutritional state which is conditioned by the appearance of complications with emphasis on sepsis. That's why it is necessary to pay special attention to the nutrition of patients with neuroictus.